Metaphysical Background of Desanka Maksimović's Collection of Poems I Seek Clemency (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Searching for the human being's grounding, Desanka Maksimović has connected religious, historical, lyrical and metahysical concepts in her collection of poems I Seek Clemency. As an artist, she has testified that men, sinful or sinless, have to be merciful, since mercy represents the very base of their human identity.
Keywords: Desanka Maksimović; I Seek Clemency; Dušan's Code; ethics; mercy